Vampyromorph coleoid predation by an ichthyosaurian from the Early Jurassic Lagerstätte of Bascharage, Luxembourg - Fischer,Valentin; Weis,Robert; Delsate,Dominique François; Della Giustina,Francesco; Wintgens,Pierre; Fuchs,Dirk; Thuy,Ben (PeerJ, 2025)
Many Early Jurassic marine predators were seemingly adapted to hunt soft and fast prey items such as cephalopods. However, deciphering what these animals ate and, therefore, the intensity of their competition is challenging, as fossilised gut content is biased by multiple factors. In this paper, we report a loligosepiid vampyromorph coleoid in the gut of a specimen of the ichthyosaurian Stenopterygius triscissus from the early Toarcian Bascharage Lagerstätte of Southern Luxembourg. This is the first report of octobrachian predation in ichthyosaurians. The coeval pachycormid teleosts Pachycormus macropterus and Saurostomus esocinus have recently been reported to feed on loligosepiid octobrachians as well. We use this opportunity to compare the functional anatomy of these taxa and re-evaluate the affinities of coleoids preserved as ichthyosaurian gut content.
Keywords: Trophic interaction; Palaeoecology; Gut content; Thunnosauria; Octobrachia; Functional anatomy